The Influence of Using Electronic Devices in the Household - Arnold Robert Rondonuwu; Vincent Landang; Kristo Andisi; Marsha Dolongseda; Julio Mamuko; Geovani Pangayouw (Syntax Corporation Indonesia, 2025)
Rapid technological developments have brought significant changes to everyday life, especially in the household environment. Electronic devices such as televisions, computers, refrigerators, washing machines, microwaves and air conditioners are now basic necessities in many households. Using these tools not only makes daily work easier, but also improves comfort and quality of life. This research aims to analyze the influence of the use of electronic devices in the household on electrical energy consumption and occupant behavior patterns. Electronic devices such as televisions, washing machines, air conditioners, refrigerators and other appliances are increasingly becoming an important part of everyday life, but inefficient use can cause a significant increase in energy consumption. This research uses a survey method of 10 or more households in a certain area to determine the frequency and duration of use of various electronic devices, as well as the level of awareness of respondents regarding energy consumption. The research results show that the most widely used electronic devices are televisions and air conditioners, with the largest contribution to electricity consumption coming from air conditioning (AC). In addition, it was found that household residents’ awareness of energy consumption is still low, even though there is interest in using energy-saving equipment. This research recommends further education regarding the efficient use of electronic devices and the importance of choosing devices that are labeled energy efficient to reduce household electricity loads. It is hoped that the results of this research can become the basis for formulating policies related to energy efficiency in the household sector.